The king's magicians - Khan, Saniyasnain; Chatterjee, Chaitali (Goodword Books New Delhi, 2010)
The King's Magicians is an enchanting tale of intrigue and adventure that follows a group of talented magicians who use their skills to navigate challenges, uncover secrets, and ultimately prove that true magic lies in creativity and collaboration.